Rapid Characterization of Spores of Bacillus cereus Group Bacteria by Matrix-Assisted Laser Desorption-Ionization Time-of-Flight Mass Spectrometry - Ryzhov, Victor (American Society for Microbiology, 2000)
Matrix-assisted laser desorption-ionization (MALDI) time-of-flight mass spectrometry was used to characterize the spores of 14 microorganisms of the Bacillus cereus group. This group includes the four Bacillus species B. anthracis, B. cereus, B. mycoides, and B. thuringiensis. MALDI mass spectra obtained from whole bacterial spores showed many similarities between the species, except for B. mycoides. At the same time, unique mass spectra could be obtained for the different B. cereus and B. thuringiensis strains, allowing for differentiation at the strain level. To increase the number of detectable biomarkers in the usually peak-poor MALDI spectra of spores, the spores were treated by corona plasma discharge (CPD) or sonicated prior to MALDI analysis. Spectra of sonicated or CPD-treated spores displayed an ensemble of biomarkers common for B. cereus group bacteria. Based on the spectra available, these biomarkers differentiate B. cereus group spores from those of Bacillus subtilis and Bacillus globigii. The effect of growth medium on MALDI spectra of spores was also explored.